Jewish Studies Quarterly (JSTOR)
Founded in 1993. The Jewish Studies Quarterly publishes studies on all aspects of Jewish history and culture. By focusing on the whole spectrum of Jewish life and thought, JSQ aims to contribute to a better understanding of Judaism. The articles cover both specialised studies and more general or interdisciplinary ones. The journal is published quarterly.
Keywords: Jewish Studies